Análisis multitemporal de la zona de explotación minera y quema de carbón a cielo abierto en la localidad de ciudad bolívar, Bogotá D.C. (2023)
Mining activities and the use of natural materials have been increasing in Colombia, generating controversy between government entities and the surrounding population regarding the indices and information that is crossed between the development economy of the country with respect to environmental and social effects (Reina, 2008). Bogota Being the capital of the country, it has an extension of 201,966 hectares of which 76.5 % is rural and 23.5% urban, and presents 21 compatible zones to carry out processes of mining exploitation, most located in rural areas (Chaves, 2018). The city will It is divided into 20 locations where 3 present mining activities, being Ciudad Bolívar, the main exploitation town where the Mochuelo industrial mining park (Garzón Tovar, 2013).